Implementing the Contextual Teaching and Learning (CTL) Learning Model in Indonesian Language Learning in Elementary Schools - Melsandra Amanda Putri; Irawan Suprapto; Yasinta Mahendra (LPPM Undiksha, 2025)
Lack of meaningful learning activities impacts low learning outcomes. This study aims to evaluate the effectiveness of the CTL model in Indonesian language learning in elementary schools. The method used was a Systematic Literature Review (SLR) for the period 2020-2024. Research selection was carried out in stages using the PRISMA flowchart to ensure transparency. Literature searches were conducted through scientific databases such as PubMed, Scopus, and Web of Science with a comprehensive search strategy using keywords and Boolean operators. The results of the analysis are presented narratively, supplemented by visual data such as graphs and tables, to increase clarity and support the study's conclusions. The research findings indicate that the implementation of the CTL model has a positive impact on Indonesian language learning in three main aspects: improved student learning outcomes, language skills (reading, speaking, and writing), and motivation and active participation. The results of this study indicate that the CTL approach can be an effective strategy for improving the quality of learning at the elementary school level. Hence, it needs to be integrated into the curriculum and training for teachers for optimal implementation. Thus, the CTL approach is an effective learning strategy for improving the quality of Indonesian language learning in elementary schools as a whole.